CRIMINAL ACTS OF WIVE'S ABANDONMENT BASED ON LAW NUMBER 23 OF 2004 CONCERNING ELIMINATION OF VIOLENCE IN HOUSEHOLD (Analysis of Judgment 85/pid.sus/2019/PN.sbh) - Aulia Rahman Hakim Hasibuan (RADJA PUBLIKA, 2023)
One form of crime that occurs in the household environment is domestic violence (KDRT). The thing that is dreamed of by a couple in a marriage is to form a family that is able to provide eternal happiness and create harmony and peace besides having children in accordance with Law Number 1 of 1974 concerning Marriage. Regarding the elimination of domestic violence, it is regulated in Law Number 23 of 2004. Today household neglect of wives is still common, although various efforts have been made to reduce or even overcome it. Based on this, the problem arises what factors cause neglect in the household and how to punish perpetrators of domestic violence. Then research is needed, namely the type of empirical legal research. In this case law is conceptualized as an empirical phenomenon that can be observed and researched in the field. Factors that cause neglect in the household are economic problems, infidelity and behavioral factors. The problem of sentencing from the analysis of cases of neglect in the household raised the conviction of the defendant with a very light 6 month prison sentence that should have been.